Deep Washington photometry of inconspicuous star cluster candidates in the Large Magellanic Cloud - Choudhury, Samyaday (2015)
We present deep Washington photometry of 45 poorly populated star cluster candidates in the Large Magellanic Cloud (LMC). We have performed a systematic study to estimate the parameters of the cluster candidates by matching theoretical isochrones to the cleaned and dereddened cluster color-magnitude diagrams. We were able to estimate the basic parameters for 33 clusters, out of which 23 are identified as single clusters and 10 are found to be members of double clusters. The other 12 cluster candidates have been classified as possible clusters/asterisms. About 50% of the true clusters are in the 100-300 Myr age range, whereas some are older or younger. We have discussed the distribution of age, location, and reddening with respect to field, as well as the size of true clusters. The sizes and masses of the studied sample are found to be similar to that of open clusters in the Milky Way. Our study adds to the lower end of cluster mass distribution in the LMC, suggesting that the LMC, apart from hosting rich clusters, also has formed small, less massive open clusters in the 100-300 Myr age range.